Are the Psychosocial Support Needs of Western Australians with Advanced Cancer and their Carers being met? A Mixed Methods Investigation of the Provision and Utilisation of Psychosocial Support for People Living with Advanced Solid Tumour Cancers and their Carers - Newton, Jade C. (Curtin University, 2023)
This hybrid thesis explored the psychosocial needs of Western Australians with advanced cancer, using a mixed methods approach. Findings revealed diverse unmet needs and varying awareness of available supports. Recommendations include improving continuity of care, education campaigns, increased support for cancer nurse coordinators, routine collection of patient-reported outcomes, and transparent cost discussions. The study emphasizes the importance of addressing psychosocial needs and enhancing accessibility to support services for individuals with advanced cancer and their caregivers.